الخصائص العزلية للجسم الصلب - لجدل, محمد العيد; خماس, عمر (university of eloued جامعة الوادي, 2014)
Due to the lack of references in theme of our research that is on the insulation properties of solids and the dispersion of information associated with it, we tried in this research to simplify the following concepts : Firstly, we defined the insulator and mentioned the physical coefficients related with it: permittivity electric, displacement of Insulation, the dielectric constant, the electrical susceptibility and we dealt with the definition of electric dipole and the definition of polarization, where we studied it in two viewpoints; microscopic and macro-scopic. Also, we studied the polarization types: electronic polarization, ionic polarization and oriented polarization. Then ; we studied the effect of an alternating electric field on the dielectric constant where it was composite and we gave its relation with insulation loss and the angle of loss. Then, we studied the relation between the composite dielectric constant and polarization with its three types: electronic and ionic and oriented, through microscopic viewpoint. Finally, we identify the relation between of dielectric constant and refractive index.نظرا لقلة المراجع في موضوع بحثنا الذي يتعلق بالعزل خصائص المواد الصلبة وتشتت المعلومات المرتبطة بها ، حاولنا في هذا البحث لتبسيط المفاهيم التالية: أولاً ، حددنا العازل وذكرنا المعاملات الفيزيائية ذات الصلة معها: السماحية الكهربائية ، إزاحة العزل ، ثابت العزل ، ال القابلية الكهربائية وتناولنا تعريف ثنائي القطب الكهربائي و تعريف الاستقطاب حيث درسناه من وجهتي نظر. المجهرية و بالعين المجردة. كما درسنا أنواع الاستقطاب: الاستقطاب الإلكتروني ، الاستقطاب الأيوني والاستقطاب الموجه. ثم ؛ درسنا تأثير المجال الكهربائي المتناوب على ثابت العزل الكهربائي حيث كان مركبًا ونحن أعطت علاقتها بفقدان العزل وزاوية الخسارة. ثم درسنا العلاقة بين ثابت العزل الكهربائي المركب والاستقطاب بثلاثة الأنواع: الإلكترونية والأيونية والموجهة ، من خلال وجهة نظر مجهرية. أخيرًا ، حددنا العلاقة بين ثابت العزل والانكسار
مذكرة ليسانس فيزياء
Keywords: ثابت العزل الكهربائي - الاستقطاب - ثنائي القطب الكهربائي - القابلية الكهربائية - الكهربائية السماحية - معامل الانكسار; Dielectric constant - polarization - electric dipole - electric susceptibility - electric permittivity - the refractive index.